¿Existe una cultura de violencia política en el País Vasco? = Is there a culture of political violence in the Basque Country? - Guibet Lafaye, Caroline (Oñati Socio-Legal Series, 2024)
An analytical tradition considers political violence linked to ethno-nationalist claims from a culturalist approach, which intends to offer a relevant interpretative model. This article aims to test this type of approach to the conflict in the Basque Country. In order to examine the validity of this interpretative model, we conducted a qualitative sociological survey among 73 former clandestine militants. The empirical data allow us to conclude that a culturalist and essentialist approach of the use of political violence in this case is irrelevant. On the other hand, we will show the interest of an analysis of the symbolic production of armed groups that gives a prominent place to the motives of resistance and national liberation.